Statystyka a etyka - Wyżnikiewicz, Bohdan (Annales. Etyka w Życiu Gospodarczym, 2015)
The article concerns ethical rules complied with both by public statistics and usersof public statistics. Ethical rules in statistics are partly codified in the EuropeanStatistics Code of Practice published by Eurostat, the statistical bureau of the EuropeanUnion. Implementation of this code is subject to periodical reviews. Thesecond part of the paper deals with various manipulations of statistical data performedby its users. The thesis of the paper states that if non-ethical practicesappear, either in public statistics or in manipulations by users, they are relativelyquickly denounced. This thesis is supported by some empirical facts.